Dronedarone vs. placebo in patients with atrial fibrillation or atrial flutter across a range of renal function: a post hoc analysis of the ATHENA trial. Issue 4 (27th December 2021) - Vamos, Mate; Oldgren, Jonas; Nam, Gi-Byoung; Lip, Gregory Y H; Calkins, Hugh; Zhu, Jun; Ueng, Kwo-Chang; Ludwigs, Ulf; Wieloch, Mattias; Stewart, John; Hohnloser, Stefan H
Abstract: Aims: Use of antiarrhythmic drugs (AADs) in patients with chronic kidney disease (CKD) is challenging owing to issues with renal clearance, drug accumulation, and increased proarrhythmic risks. Because CKD is a common comorbidity in patients with atrial fibrillation/atrial flutter (AF/AFL), it is important to establish the efficacy and safety of AAD treatment in patients with CKD. Methods and results: Dronedarone efficacy and safety in individuals with AF/AFL and varying renal functionality [estimated glomerular filtration rate (eGFR): ≥60, ≥45 and <60, and <45 mL/min] was investigated in a post hoc analysis of ATHENA (NCT00174785), a randomized, double-blind trial of dronedarone vs. placebo in patients with paroxysmal or persistent AF/AFL plus additional cardiovascular (CV) risk factors. Log-rank testing and Cox regression were used to compare the incidence of endpoints between treatments. Overall, 4588 participants were enrolled from the trial. There was no interaction between treatment group and baseline eGFR assessed as a continuous variable ( P = 0.743) for the first CV hospitalization or death from any cause (primary outcome). This outcome was lower with dronedarone vs. placebo across a wide range of renal function. First CV hospitalization and first AF/AFL recurrence were both lower in the two least renally impaired subgroups with dronedarone vs. placebo. Treatment emergent adverse events leading to treatment discontinuation were more frequent with dronedarone vs. placebo and occurred more often in patients with severe renal impairment. Conclusion: Dronedarone is an effective AAD in patients with AF/AFL and CV risk factors across a wide range of renal function. Graphical Abstract: